Nuclear-Cytoplasmic Shuttling of Chibby Controls β-Catenin Signaling - Li, Feng-Qian (The American Society for Cell Biology, 2010)
In the canonical Wnt pathway, β-catenin acts as a key coactivator that stimulates target gene expression through interaction with Tcf/Lef transcription factors. Its nuclear accumulation is the hallmark of active Wnt signaling and is frequently associated with cancers. Chibby (Cby) is an evolutionarily conserved molecule that represses β-catenin–dependent gene activation. Although Cby, in conjunction with 14-3-3 chaperones, controls β-catenin distribution, its molecular nature remains largely unclear. Here, we provide compelling evidence that Cby harbors bona fide nuclear localization signal (NLS) and nuclear export signal (NES) motifs, and constitutively shuttles between the nucleus and cytoplasm. Efficient nuclear export of Cby requires a cooperative action of the intrinsic NES, 14-3-3, and the CRM1 nuclear export receptor. Notably, 14-3-3 docking provokes Cby binding to CRM1 while inhibiting its interaction with the nuclear import receptor importin-α, thereby promoting cytoplasmic compartmentalization of Cby at steady state. Importantly, the NLS- and NES-dependent shuttling of Cby modulates the dynamic intracellular localization of β-catenin. In support of our model, short hairpin RNA–mediated knockdown of endogenous Cby results in nuclear accumulation of β-catenin. Taken together, these findings unravel the molecular basis through which a combinatorial action of Cby and 14-3-3 proteins controls the dynamic nuclear-cytoplasmic trafficking of β-catenin.